2021
DOI: 10.1149/1945-7111/ac239c
|View full text |Cite
|
Sign up to set email alerts
|

Glyme-Lithium Bis(trifluoromethylsulfonyl)amide Super-concentrated Electrolytes: Salt Addition to Solvate Ionic Liquids Lowers Ionicity but Liberates Lithium Ions

Abstract: Solvate ionic liquids (ILs) such as binary equimolar mixtures of glymes (ethyleneglycol-dimethylether or CH3(OCH2CH2) n OCH3) and lithium bis(trifluoromethylsulfonyl)amide (LiTf2N; Tf = SO2CF3) are known to show identical self-diffusion coefficients for glymes and Li+ ions. Here, we report that the addition of LiTf2N to the solvate ILs drastically changes their electrolyte properties. When the lithium salts are added to give the super-concentrated electrolytes with [O]/[L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The role of the TFSI À anions is therefore significant in this lithium hopping mechanism as the latter ratio has a slightly lower diffusion coefficient. Although this type of hopping mechanism has been previously hypothesised in the literature, 54 no direct evidence to support this has been reported to date. Simulations at elevated temperatures of 227 1C and 427 1C do not represent the real system at 30 1C and 80 1C but provide supportive evidence of a likely mechanism hypothesised by experiment.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 84%
“…The role of the TFSI À anions is therefore significant in this lithium hopping mechanism as the latter ratio has a slightly lower diffusion coefficient. Although this type of hopping mechanism has been previously hypothesised in the literature, 54 no direct evidence to support this has been reported to date. Simulations at elevated temperatures of 227 1C and 427 1C do not represent the real system at 30 1C and 80 1C but provide supportive evidence of a likely mechanism hypothesised by experiment.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 84%
“…17-19) using experimental eNMR species velocities in electrolytes comprising mixtures of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt dissolved in tetraglyme. [38][39][40][41] Unlike Eq. 3 wherein t 0 + is determined from all three species velocities, Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…35−37 The distinct Li + solvation structures in HCEs are responsible for the atypical electrolyte properties, such as the enhanced oxidative stability, 23,34 thermal stability, 38 and improved Li + transport. 34,39,40 Solvate ionic liquids (SILs) have been shown to have similar properties to HCEs and ionic liquids (IL). 41−44 These properties include thermal stability, 45 a wide electrochemical stability window, and the ability to withstand high anodic voltages of up to 5 V. 34 Moreover, previous studies have also shown that SILs are able to inhibit the corrosion of Al current collectors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, it appears that there is a trade-off between transfer number and ionic conductivity and that a balanced Li + transport would be achieved with anions of moderate Lewis basicity, such as BF4 − , OTf − and likely SCN − , further justifying the investigation of such systems. Finally, attempts have been made to improve the SILs properties by adding an excess of the lithium salt to convert them to HCEs (i.e., [O]/[Li] < 4) . These HCE-SIL electrolytes have been shown to have improved oxidative stability and Li + transport but low ionic conductivity due to their high viscosities. , These studies demonstrate that to enhance the ionic transport of SILs and HCE-SILs while maintaining their advantageous electrochemical properties, it is critical to have a molecular understanding of the influence of ion–solvent and ion–ion interactions on their transport properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation